Recovery of local dragonfly diversity following restoration of an artificial lake in an urban area near Buenos Aires - Lozano, Federico (2022)
Urban lakes are environments prone to severe environmental deterioration if an effective management policy is not carried out by local governments. However, management aimed only at facilitating access and recreation for citizens can negatively affect the environmental health of these ecosystems since the pristine ecosystem structure is not recovered. In this paper we present early results of a governmental restoration program based on pond cleaning and native vegetation recovery at an artificial lake of the city of Avellaneda (Saladita Norte Reserve), part of the Metropolitan Area of Buenos Aires, one of the largest urban areas with the highest concentrations of inhabitants of the world. We used odonates as indicators because of their quick response to changes in environmental quality. Besides, we tested if the NDVI can be used as a surrogate to monitor changes in dragonfly diversity in managed areas. Since the intervention was carried out during the winter and there were no previous data on the richness or diversity of odonates, we analyzed their response to the intervention comparing it with a lake of similar origin and characteristics but with a different use and management (Saladita Sur Reserve). We recorded in Saladita Norte 81% of the regional diversity, including three newly recorded species, while the lake Saladita Sur, only amounted to 21% of the regional diversity. The NDVI did not reflect the observed changes in the structural complexity of the vegetation and therefore could not be used as a surrogate. These early results indicate that management practices such as the increase of native vegetation on the banks (especially in grassland areas), keeping a diverse floating vegetation and the cleaning and removal of wastes from the water, promote a significant and rapid increase in the levels of biodiversity.